2005
DOI: 10.1186/1471-2458-5-28
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study to identify community structures for management of severe malaria: a basis for introducing rectal artesunate in the under five years children in Nakonde District of Zambia

Abstract: Background: Malaria is a serious illness among children aged 5 years and below in Zambia, which carries with it many adverse effects including anemia and high parasites exposure that lead to infant and childhood mortality. Due to poor accessibility to modern health facilities, malaria is normally managed at home using indigenous and cosmopolitan medicines. In view of problems and implications associated with management of severe malaria at home, rectal artesunate is being proposed as a first aid drug to slow d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
3
15
0
1
Order By: Relevance
“…Our findings reveal that the study communities were familiar with rectal application of medicine, mainly traditional medicine but also biomedical, an observation reported by Kaona and Tuba [11] from Zambia, arguing well for the potential acceptability of rectal artesunate.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our findings reveal that the study communities were familiar with rectal application of medicine, mainly traditional medicine but also biomedical, an observation reported by Kaona and Tuba [11] from Zambia, arguing well for the potential acceptability of rectal artesunate.…”
Section: Discussionsupporting
confidence: 67%
“…We know far less through research about how families manage severe malaria which carries a higher mortality, except that convulsions tend to be perceived as a different disease with a separate aetiology [8][10]. Crucially, we know little, except for very recent work, about the nature and reason for delays involved between presentation of danger signs and arrival at hospital and/or provision of antimalarial treatment to children in Sub-Saharan Africa - an important basis for reducing this interval and improving child survival [11][13].…”
Section: Introductionmentioning
confidence: 99%
“…At the time of writing, only one other published study has addressed this issue. 18 The present study adds to preliminary qualitative ethnographic research of maternal perceptions and practices regarding childhood fever to provide a context with which to guide future implementation of this intervention. The findings of the preliminary research showed that mothers were adept at recognizing febrile illness, which was often managed expectantly with traditional home treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The child's mother made the decision in only 7.4% of cases (Okoko & Yamuah, 2006). Less commonly, authors have reported that mothers have the autonomy to diagnose and treat malaria themselves, such as in a study in Zambia (Kaona & Tuba, 2005). A study of care-seeking in rural Senegal found that decision-making was collaborative in 71% of cases requiring treatment outside the home, with household roles divided according to gender norms, inter-generational relations and family characteristics (Frankel & Lalou, 2009).…”
Section: Introductionmentioning
confidence: 99%